TRADITIONAL SINGING: ROOTS OF UZBEK MUSICAL CULTURE - Ma’rufjon Xalilov (Web of Journals Publishing, 2025)
This scientific article explores the formation, historical evolution, and current state of traditional Uzbek vocal art. It examines major regional performance schools — Bukhara, Fergana-Tashkent, and Khorezm — analyzing their stylistic characteristics. The study also investigates the connection between vocal performance and maqom music, the role of the master-apprentice system, and the contribution of female singers. Traditional singing is presented as a core component of the national musical identity and intangible cultural heritage of Uzbekistan.
Keywords: Traditional singing, Uzbek music culture, vocal performance, regional schools, maqom, master-apprentice tradition, poetic repertoire, female singers, intangible heritage, national identity.